The potential role of PIWI-interacting RNAs in non-small cell lung cancer - Song, Linqian; Zhou, Jian-Guo; Ma, Hu (Frontiers in Oncology, 2025)
Non-small cell lung cancer (NSCLC) accounts for approximately 85% of lung cancer and remains the leading cause of cancer mortality globally. The lack of early diagnostic tools and effective therapeutic targets contributes to poor outcomes for NSCLC patients. PIWI-interacting RNA (piRNA), a short-stranded non-coding RNA, interacts with PIWI proteins to epigenetically regulate gene expression. Recently, much evidence suggests that piRNAs and PIWI proteins are closely associated with NSCLC progression, including cancer cell proliferation, metastasis, chemoresistance, and stemness. Therefore, piRNAs and PIWI represent promising biomarkers and therapeutic targets, showing excellent sensitivity and specificity. However, their precise functions and potential mechanisms remain incompletely understood. Thus, it is necessary to further elucidate the mechanism of piRNAs/PIWI role and enhance clinical translation. This review synthesizes the biosynthesis and function of piRNAs, as well as the regulatory mechanisms of piRNAs/PIWI in NSCLC. Additionally, we evaluate the clinical potential of the piRNAs and PIWI as novel biomarkers and therapeutic targets in NSCLC. This provides new insights into the diagnosis and treatment of NSCLC.